New Developments in the Management of Borderline Resectable Pancreatic Cancers - Goodman, Martin David; McPartland, Sarah; Huber, Kathryn; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
There remains great variability in the treatment for patients with borderline resectable pancreatic head cancers. Whether surgery should be attempted or neoadjuvant therapy consisting of chemoradiation or chemotherapy alone is at some debate. Each neoadjuvant regimen does show efficacy but there is no clear consensus which would be most beneficial. We will discuss three abstracts (#4043, #4057, #e15082) that were presented in the 2013 ASCO Annual Meeting that will discuss neoadjuvant therapies and how they are related to getting an R0 resection. Image: Main atrium of Tufts Medical Center on the day of its renaming (March 4, 2008). Boston, MA, USA.